The quality of institution and foreign direct investmnet (FDI) in Malaysia - Zulkefly Abdul Karim,; Mohd Azlan Shah Zaidi,; Mohd Adib Ismail,; Bakri Abdul Karim, (FEP, 2012)
Since the 1990’s, institutional factors have been regarded as playing important roles in stimulating foreign direct investments (FDI). However, empirical studies on their importance in affecting FDI are still lacking, especially in regards to small open economies. This paper attempts to investigate the role of institutions in regards to the inflow of FDI in Malaysia’s small open economy of Malaysia. Using the bounds testing approach (ARDL model), empirical findings reveal that a long-run relationship exists between FDI and institutional variables. Several institutional variables are found to play prominent roles in influencing the inflow of FDI, namely governmental stability, bureaucracy and corruption. Thus, providing and maintaining the quality of domestic institutions alongside the implementation of FDI friendly policies would be beneficial to Malaysian economic growth stemming from foreign investment.